DEEP BRAIN STIMULATION IN INTRACTABLE SHORT-LASTING UNILATERAL NEURALGIFORM HEADACHE ATTACKS: A MULTICASE SERIES. Issue 11 (14th October 2015) - Miller, Sarah; Zrinzo, Ludvic; Matharu, Manjit
Abstract : Introduction: SUNCT and SUNA are primary headache conditions characterized by short lasting attacks of unilateral pain accompanied by autonomic features. Neuroimaging studies have suggested a role of the posterior hypothalamus in its pathogenesis. Aim: Previous case reports on deep brain stimulation (DBS) of the midbrain tegmentum (just posterior to the hypothalamus) for SUNCT/SUNA are limited to a total of three patients. We present clinical data on eight new patients treated with DBS. Method: Eight patients underwent midbrain tegmentum DBS with an MRI-guided and verified approach. The target lay between the mammillothalamic tract and the anteromedial quadrant of the red nucleus. Headache diaries were used to monitor response. Results: The median follow up period was 20 months. Median improvement in attack frequency was 70%. Seven patients obtained a 30% or more reduction in attack frequency at final follow up. At final follow up, one patient had the stimulator off. Seven out of eight patients would opt to have the stimulator again and all would recommend to others. Conclusion: Midbrain tegmentum DBS may be a useful treatment in intractable SUNCT. It should be reserved only for patients failing all other medical and surgical treatment options.